PIAGAM MADINAH: LANDASAN MANAJEMEN DAN RELEVANSI DAKWAH ISLAM KONTEMPORER - Hartoyo, Hartoyo; Habibi, Rohim; Sariman, Sariman (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2024)
The Medina Charter, also known as the Medina Constitution, has an important meaning in Islamic history that lays the foundation of contemporary Islamic da'wah management, this article discusses how the Medina Charter is still relevant in the development of Islam, this research uses a descriptive qualitative approach with data obtained from library research. The results of this research are as follows: The Medina Charter is an important value in creating a cohesive society and understanding each other. Medina Charter education helps a framework that enhances cooperation and mutual understanding among individuals. Medina Charter education can encourage positive change and conflict around the world. It leads to da'wah practices that must build between different people. In the management of da'wah, the Charter of Medina causes justice, tolerance, and remorse in the game, which forms a da'wah practice that forms highlights positive and negative reinforcement, and forms inspiration and guidance for making communities.